Design of a universal device holder system - Tóth, Dániel (Design of Machines and Structures, 2023)
During the performance of the dust chamber tests, the device systems must meet not only mechanical but also flow aspects, for this reason a special system –which cannot be used on other test equipment– must be developed to perform the dust tests. During the development of the concept of the modular device system (MDDT: Modular Device for Dust Test) designed for carrying out dust chamber tests, the design methods based on function analysis, used in the design of production equipment, can be well applied.